Long-Term Cryopreservation of 2-Cell Stage Embryos in ICR/Mlac-Hydro and ICR/Mlac-Free Hydro Mice at the National Laboratory Animal Center, Mahidol University - ฺBuaban Theerapong (Burapha Science Journal, 2026)
Background and Objectives : The National Laboratory Animal Center, Mahidol University, is a source of laboratory animal production for research in Thailand. ICR/Mlac-hydro and ICR/Mlac-free hydro mice were developed as an animal model for hydronephrosis in humans. Additionally, these mouse strains have been preserved in the embryo bank since 2014. To prevent the loss of mouse strains, ensure the stability of laboratory animals, increase the diversity of mouse strains, develop the science of laboratory animal, reduce the import of expensive laboratory animals, and reduce the costs of laboratory animal breeding. However, the production of these mouse strains has been discontinued as research using these animals has been completed. To ensure that the new colony of ICR/Mlac-hydro and ICR/Mlac-free hydro mice can be established in the future. Therefore, 11-year frozen 2-cell stage embryos of ICR/Mlac-hydro and ICR/Mlac-free hydro mice will be tested by the thawing to determine the percentage of survival 2-cell stage embryos (% survival). The survival 2-cell stage embryos of ICR/Mlac-hydro and ICR/Mlac-free hydro mice were used for embryo transfer in recipients to determine the percentage of newborns (% newborn). After that, a pair of newborns in each mouse strain was tested for fertility with natural mating. Methodology : This study was approved by the National Laboratory Animal Center-Animal Care and Use Committee (NLAC-ACUC, protocol no. AP2024-02). All animal procedures were conducted at the Association for Assessment and Accreditation of Laboratory Animal Care (AAALAC) International. All mice were maintained under routine husbandry procedures in the animal room with strict hygienic conventional, controlled temperature at 22±3ºC, 30-70% humidity, 14 hours light conditions (lights on from 6:00 AM to 8:00 PM), 5-7 ppm choline reverse osmosis water, and a standard mouse diet. Mice had access to diet and water at all times (ad libitum). Mice are kept in plastic cages and stainless-steel lids. The sterile bedding used consisted of corn cobs and dried water hyacinth. Before thawing, the culture plate was prepared with M16 medium on a 35 mm sterile plastic dish consisting of a 3 drop of wash drop (50 µl), and a culture drop (150 µl) covered with mineral oil in a CO2 incubator, overnight. The next morning, the 0.25 ml straw tube was removed from the liquid nitrogen tank, warmed at room temperature for 20 seconds, then warmed in a 37ºC water bath for 20 seconds. The 0.25 ml straw tube was cut with sterilized scissors, and the 2-cell stage embryos, along with 35EG and 0.3 M Trehalose, were released into a 35 mm sterile plastic dish. 30 seconds later, the embryos were found under a stereomicroscope and thawed using a 50 µl of 37°C 0.3 M Trehalose for 3 minutes, a 50 µl of 37°C 0.15 M Trehalose for 3 minutes, a 50 µl of 37°C 0.075 M Trehalose for 3 minutes, and a 50 µl of 37°C Holding medium for 5 minutes. Embryos were washed in 50 µl of M2 medium 3 times and washed in a wash drop 3 times. The survival 2-cell stage embryos were cultured in a 150 µl culture drop in a CO2 incubator, waiting for embryo transfer. The survival 2-cell stage embryos were used for transfer to the oviducts of recipients. The recipients were natural-born on days 19-20 after embryo transfer. The newborns were set to mate at 7 weeks of age. Main Results : The thawing of 157 embryos in ICR/Mlac-hydro mice. The results show that 142 embryos were recovered under a stereomicroscope, and then 48 embryos were found dead. Ninety-four of the 2-cell stage embryos were alive, with the percentage of survival 2-cell stage embryos was 59.9 (94/157). In ICR/Mlac-free hydro mice, 208 embryos were thawed, and 196 embryos were discovered. After that, 88 embryos were determined to be dead. 108 of the 2-cell stage embryos were alive, with the percentage of survival 2-cell stage embryos being 51.9 (108/208). The percentage of survival 2-cell stage embryos did not differ significantly between the two mouse strains (Fisher’s Exact Test, P>0.05). The embryo transfer of survival 2-cell stage embryos. In ICR/Mlac-hydro mice, the 94 survival embryos were transferred to 8 recipients. 19-20 days later, the number of newborns was 7, 8, 6, and 8 in recipients no. 3, 4, 6, and 8, respectively. The percentage of newborns was 30.9 (29/94), consisting of 19 males and 10 females. For ICR/Mlac-free hydro mice, 108 of the survival 2-cell stage embryos were transferred to 7 recipients. The number of newborns was 7 and 4 in recipients no. 10 and 13, respectively. The percentage of newborns was 10.2 (11/108), including 7 males and 4 females. However, the percentage of newborns differed significantly between the two mouse strains (Fisher’s Exact Test, P<0.05). After natural mating of each mouse strain, ICR/Mlac-hydro mice gave birth to 6 offspring, including 3 males and 3 females. In ICR/Mlac-free hydro mice, 7 offspring were born, consisting of 3 males and 4 females. Conclusions : The embryo bank can preserve the strains of ICR/Mlac-hydro and ICR/Mlac-free hydro mice. The 11-year-frozen 2-cell stage embryos survive after thawing and will be born after embryo transfer. Mice can give birth naturally and are sufficient for establishing the new colony.